2020
DOI: 10.46743/2160-3715/2020.4099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media Addiction on Employees’ Wellbeing and Work Productivity

Abstract: The objective of this study is to gain insights into the experiences of employees regarding their social media usage and consequences of social media overuse at the workplace. Fourteen semi-structured interviews were conducted, audio-recorded, transcribed, and analyzed using the Interpretative Phenomenological Analysis (IPA) procedures. The qualitative data was collected from the employees working in renowned IT/ITES companies in India. The themes that emerged are lack of sleep; backache and eye strain; feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Moreover, a study [ 69 ] conducted in a Tech based company in India also revealed that employees engaged in too much social media usage were having sleep deprivation; eye strain; feeling of resentment; lack of depth in the relationships; compromise with the work quality, and a distraction from work. Another study among social media users observed a number of physical, psychological and behavioural issues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study [ 69 ] conducted in a Tech based company in India also revealed that employees engaged in too much social media usage were having sleep deprivation; eye strain; feeling of resentment; lack of depth in the relationships; compromise with the work quality, and a distraction from work. Another study among social media users observed a number of physical, psychological and behavioural issues.…”
Section: Discussionmentioning
confidence: 99%
“…Social media also affects adolescents. Studies show that 95%of 12-17-year-old teenagers are now online, and 80% of them are social media users [13]. Moreover, 22% of teenagers use their preferred social media sites more than 10 times per day [14].…”
Section: Well-being Of Adolescentsmentioning
confidence: 99%
“…The exponential growth of SM usage worldwide has significantly altered how organizations interact with their various internal and external stakeholders (Bakar et al., 2019). SM is a cluster of web‐based applications that enable users to create and share content with others (Priyadarshini et al., 2020). SM usage in an organization facilitates knowledge sharing and interactions between teams regardless of their physical location (Ali et al., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%